Model Latihan Kelincahan Tendangan Sabit Pencak Silat Menggunakan Alat Bantu Ladder Drill - Dinda Chantika Herdiman; Johansyah Lubis; Yusmawati (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
ABSTRACT This study aims to produce a product in the form of a sabit kick training model in pencak silat, so this research can be a reference source for trainers as a variation of the sabit kick exercise. This research uses Research & Development development research. Of the ten steps of the ADDIE model, in the ADDIE model research there are 5 stages of the research process, namely Analysis, Design, Model Development, Implementation, Evaluation. In this study, researchers collaborated with one academic expert (lecturer) and two non-academic experts (coach). The subject of this study was the IPSI pencak silat athlete in Tangerang City and was the subject of a small group trial. The validation test used in this study was using the expert justification test, where the training model that had been created and developed was tested and then consulted and assessed by experts. Through validation tests carried out using expert justification tests produced products in the form of a pencak silat sickle kick training model. The training model can be developed to be more varied. There are 13 training models developed. Keywords: training model, scythe kick, pencak silat